Effects of CuO on glass prepared from local sand in Nakhon Pathom Province - Rachniyom, Watcharin; Sangwaranatee, Narong; Kaewkhao, Jakrapong (Interdisciplinary Research Review, 2018)
In this work, sand was obtained from pit sand in district Kamphaeng Saen, Nakhon Pathom province. This sand was investigated the chemical compositions and the crystal structures before use it as raw material to prepare glass samples. The glass samples were prepared in compositions of (49-x)SiO2: 7.5B2O3 : 8CaO : 10SrO2: 0.5Sb2O3 : 25Na2O : x CuO (where x = 0.0 , 0.2 , 0.4 , 0.6 , 0.8 , 1.0 mol%) by melt quenching technique. After that, all glasses were cut and polish in proper shape for measurement in density, refractive index, hardness and optical properties. The results of sand sample observed major components with SiO2 (wt.%), K2O (wt.%) and Fe2O3 (wt.%). The crystalline structure of sand has shown large of quartz phase. For the results of glass sample, the density values of glasses were between 2.818–2.834 g/cm3. The refractive index values were in range 1.6523–1.6532. The Vicker’s hardness values were widely around 319.28–410.94 without relative with the increasing of CuO concentration. The absorption spectra of glasses were occurred the contamination of Co2+, Fe2+ and Fe3+ from crucibles and raw material. In addition, the effects of CuO were shown board peaks of absorption spectra around 780 nm., and they were increased with increasing of CuO concentrations. The colors of glasses were shown in green and yellow color which stronger and brightness with increasing CuO concentration.